Variations in Marine Bacterial and Archaeal Communities during an Ulva prolifera Green Tide in Coastal Qingdao Areas - Guihua Zhao; Hui He; Hualong Wang; Yantao Liang; Cui Guo; Hongbing Shao; Yong Jiang; Min Wang (Microorganisms, 2022)
Green tides caused by Ulva prolifera occur annually in the Yellow Sea, potentially influencing the marine microorganisms. Here, we focused on the variations in marine bacterial and archaeal communities during an U. prolifera green tide in coastal Qingdao areas with Illumina high-throughput sequencing analysis. Our results revealed that the diversity and structure of bacterial and archaeal communities, as well as the organization and structure of microbial co-occurrence networks, varied during the green tide. The decline phase may be favorable to the bacterial and archaeal diversity and richness. The bacterial community, as well as the archaeal community, showed clear variations between the outbreak and decline phases. A simpler and less connected microbial co-occurrence network was observed during the outbreak phase compared with the decline phase. Flavobacteriales and Rhodobacterales separately dominated the bacterial community during the outbreak and decline phase, and Marine Group II (MGII) dominated the archaeal community during the green tide. Combined with microbial co-occurrence network analysis, Flavobacteriales, Rhodobacterales and MGII may be important organisms during the green tide. Temperature, chlorophyll a content and salinity may have an important impact on the variations in bacterial and archaeal communities during the green tide.